Development of Business Management and Marketing of Handy Crafts Products Based on Online Marketing Partnership Strategy - Prihandoko Prihandoko; Dyah Mieta Setyawati; Sigit Widiyanto (AIBPM Publisher, 2020)
The rapid growth of information technology and the emergence of marketplace open a lot opportunities to the micro-entrepreneurs. The purpose of this study is to assist an actor of micro-entrepreneur in dealing with broader and massive marketing effort through digital platform. Ngasti Shop is one of the micro-entrepreneur business that needs to broaden its markets. The study conducted a counselling and discussion with the owner in the development of business management and product marketing. An online shop has been created in one of the big marketplaces in the country. A good result was received, that the order of souvenirs in Ngasti Shop is increasing. It means that the use of digital platform for product marketing is valuable and urgently needed.